The lithium ion battery: From industry to diverse ecosystems - KIM, Kijong (Institutional Knowledge at Singapore Management University, 2023)
Raymond Green, Chief Researcher at Amber Global, a global energy think tank, believes that climate change could be slowed by consumers switching to electric vehicles (EVs). He analyses the lithium-ion (li-ion) battery industry’s origins and its ascendance to an ecosystem that encompasses diverse actors such as lead firms (key li-ion battery manufacturers), upstream suppliers of raw and processed minerals, and downstream complementors of battery management system (BMS) providers and charging stations. In particular, governments play integral roles as members of the li-ion battery ecosystem in which their unique ties with lead firms have led to the rise of diverse ecosystems across the countries of Japan, South Korea, and China. Consequently, the government and lead firms co-lead and also co-develop the specific li-ion battery ecosystem to align the set of multilateral actors to materialise the value proposition of high-energy and low-cost li-ion batteries for the end-user. How has the emphasis of the different governments influenced the rise of the diverse li-ion battery ecosystems and therefore, the alignment of the diverse actors? What are the strengths and weaknesses of each approach and how would it effect the emergence of the specific li-ion battery ecosystem as a winner in the future? This case may be used for graduate, postgraduate and executive education courses related to public policy, global strategy, and international business. By working through the case and assignment questions, students will have the opportunity to gain knowledge on the secondary battery industry origins and how it has developed to encompass a multitude of actors with various roles; understand the implications of non-market strategies such as government ties with lead firms on the development of diverse ecosystems and elaborate on the ecosystem-as-structure view to analyse how the lead firm and government can co-lead the ecosystem to align the set of multilateral actors to materialise the value proposition.